2022
DOI: 10.3390/su14031105
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Removal of Priority Substances and Emerging Pollutants from Stormwater: Case Study of the Kołobrzeska Collector, Gdańsk, Poland

Abstract: Progressive urban development affects environmental balance and disrupts the hydrologic cycle, in which rainfall plays a significant role. Since rainwater is considered a valuable resource of the environment, many technical solutions are implemented that enable effective rainwater management. On the other hand, stormwater runoff from urban areas contains numerous (also toxic) substances, and therefore should be properly treated. In this study, a multistage constructed wetland (MCW) pilot installation was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Significant factors limiting or even preventing the course of nitrification in the biological treatment system of the Municipal and Industrial Sewage Treatment Plant in Oświęcim are inhibitors flowing in with industrial sewage and high COD values. The list of organic and inorganic compounds having a negative effect on nitrifying bacteria is very long and includes a number of substances for which the degree of inhibition has been determined [ 6 , 13 , 17 , 19 , 20 ]. Most of these compounds were present in the sewage we analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant factors limiting or even preventing the course of nitrification in the biological treatment system of the Municipal and Industrial Sewage Treatment Plant in Oświęcim are inhibitors flowing in with industrial sewage and high COD values. The list of organic and inorganic compounds having a negative effect on nitrifying bacteria is very long and includes a number of substances for which the degree of inhibition has been determined [ 6 , 13 , 17 , 19 , 20 ]. Most of these compounds were present in the sewage we analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Municipal and industrial wastewater is a carrier of many dangerous organisms and substances, which include parasites and pathogenic organisms [ 1 , 2 , 3 ], toxic substances and compounds disturbing the natural biological balance in treated sewage receivers by increasing the saprobicity and eutrophication of these waters [ 4 , 5 , 6 ]. Such wastewater can be neutralized by mechanical–biological or mechanical–biological–chemical methods of treatment with the use of activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds analysed were: atrazine, pentachlorophenol (PCP), chlorpyrifos, 2,4-dichlorophenoxyacetic acid (2,4-D), prometon, simazine, carbaryl, nonylphenol (NP), perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorobutane sulfonic acid (PFBS) and perfluorononanoic acid (PFNA). Studies of CECs' occurrence in Poland [47] reported that rainwater runoff was characterized by variable concentrations of polycyclic aromatic hydrocarbons (benzo(a)pyrene, benzo(b)fluoranthene, phenanthrene, fluoranthene and pyrene) and microplastics. Stuk-Sokolowska et al [48] focused on low molecule benzotriazoles (BTRs) in urban road rainwater in Poland, showing that concentrations of BTRs in rainwater ranged from 4.5 µg/mL to 26.4 µg/mL.…”
Section: Parametermentioning
confidence: 99%
“…Shenzhen started using a drainage water supply system for water pollution treatment 20 years ago [150]. Using a multistage constructed wetland in Poland, heavy metals and microplastics were removed to varying degrees with the hydraulic loading of the bed [151]. In sum, the construction of rainwater storage tanks plays an important role in the protection of the urban water environment.…”
Section: Rainwater Storage Tank Treatmentmentioning
confidence: 99%